PENGGUNAAN VIDEO PEMBELAJARAN SUPERBOOK DALAM IBADAH SEKOLAH MINGGU GMIM SOLA GRATIA TIKALA DI ERA DIGITAL - Horasman Perdemunta Munthe Munthe; Brigita Tuwo Tuwo; Dessy Tarema Tarema; Rondo Enjihito; Kezia Tangdiura Tangdiura (PT. Giat Konseling Nusantara, 2025)
This research aims to determine the use of Superbook learning video media in Sunday School worship at the GMIM Sola Gratia Tikala congregation. The research approach used is a quantitative descriptive approach. There are two ways the author uses to collect research data, namely data collection techniques using interviews and observations as well as literature studies. Based on the results of data analysis, it was concluded that the use of Superbook learning videos could be an effective tool for improving the quality of Sunday school worship. However, it is important to remember to use it wisely and in balance with other teaching methods. So Sunday School teachers still have an important role in instilling Christian values ​​and guiding children on their journey of faith